GLP-1 Based Therapy for Diabetes and Potential of Thyroid Cancer - Büyükbeşe, Mehmet Akif (JOP. Journal of the Pancreas, 2014)
Despite incredible effort on understanding and awareness of diabetes, management procedure is becoming more challenging since the complications of the disease as well as the newly discovered or yet put on market drugs that may have a suspicious association with cancer. This metabolic disorder itself does already have high prevalence of cancer such as pancreas and colon. Thyroid cancer itself is also increasing and thyroid disorders associated with diabetes is well known endocrinological problem. Rise in thyroid cancer patients in diabetics are also emphasized in meta-analyses. Obesity does seem to be another factor for thyroid cancer; however, it is also commonly associated with patients who have type 2 diabetes. GLP-1 based therapy does not only help diminish blood glucose but help satiety and lose weight as well which is a desired effect of diabetes therapy since losing weight corrects many other cardiovascular risk factors. Thyroid cancer and its connectivity to GLP-1 analogue therapy is a concern, yet not proven; although may diminish the rate of prescription by some diabetologists, although some suggest outweigh the clinical positive effect. Image: Thyroid gland.